Operational Modal Analysis: A Tool for Assessing Changes on Structural Health State of Historical Constructions after Consolidation and Reinforcement Works—Jura Chapel (Jerez de la Frontera, Spain) - Manuel Romero; Pablo Pachón; Víctor Compán; Margarita Cámara; Francisco Pinto (Shock and Vibration)
Today’s society is sensitive to the architectural heritage conservation. This implies to perform works to maintain these buildings and to assure their structural security. In the last years, the structural analysis of historical masonry constructions has experienced a great progress, thanks to the use of techniques based on the study of the dynamic properties of building structures. In this context, changes on the structural health state of a building are one of the elements that can be assessed considering changes on their dynamic properties. This is useful to evaluate the effectiveness of structural interventions on this kind of buildings by analysing these properties before and after it. This paper focuses on the Jura Chapel, in Jerez de la Frontera (Spain). This chapel is part of San Juan de los Caballeros Church and is dated from the 15th century. In 2015 and after the identification of some structural damages in the chapel vault, an intervention was initiated to improve its structural behaviour and to recover its original appearance. The present work reports the evaluation of the effects that this intervention has on the structural health state of the building, using nondestructive techniques based on ambient vibration tests (AVT) and Operational Modal Analysis (OMA). The AVT were performed for both prerestored and restored states and under environmental loads. A discussion about the validity of doing AVT from extrados when a vault presents disconnection between ribs and web is included in the paper. As a result, the first five natural frequency values have increased while the corresponding mode shapes have not changed significantly. This proves a structural health improvement caused by the repairing process without changing the original behaviour of the structure. This work shows OMA capabilities for evaluating the effectiveness of intervention works on the health state of a historical masonry structure.